2007
DOI: 10.1186/1472-6807-7-66
|View full text |Cite
|
Sign up to set email alerts
|

The binding site for neohesperidin dihydrochalcone at the human sweet taste receptor

Abstract: Background: Differences in sweet taste perception among species depend on structural variations of the sweet taste receptor. The commercially used isovanillyl sweetener neohesperidin dihydrochalcone activates the human but not the rat sweet receptor TAS1R2+TAS1R3. Analysis of interspecies combinations and chimeras of rat and human TAS1R2+TAS1R3 suggested that the heptahelical domain of human TAS1R3 is crucial for the activation of the sweet receptor by neohesperidin dihydrochalcone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
113
1
7

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(129 citation statements)
references
References 45 publications
(74 reference statements)
8
113
1
7
Order By: Relevance
“…Also, sweetness inhibition was overcome at higher concentrations of sucrose and cyclamate. This observation is consistent with competitive inhibition, similar to previously studied sweet taste inhibitors (Schiffman et al 1999;Winnig et al 2007). The highest molar concentrations of sucrose and cyclamate used in this study were greater than those of acesulfame K and sucralose.…”
Section: Discussionsupporting
confidence: 77%
“…Also, sweetness inhibition was overcome at higher concentrations of sucrose and cyclamate. This observation is consistent with competitive inhibition, similar to previously studied sweet taste inhibitors (Schiffman et al 1999;Winnig et al 2007). The highest molar concentrations of sucrose and cyclamate used in this study were greater than those of acesulfame K and sucralose.…”
Section: Discussionsupporting
confidence: 77%
“…[34,35] In later work, Meyerhof and co-workers demonstrated that the T1R3 TMD is also the site for binding of the sweetener neohesperidin dihydrochalcone. [36] 2006: The Three Binding Site Sweetener Receptor Model. A collaborative team of the Max, Margolskee, and Osman groups developed a model of the T1R2/T1R3 receptor where some small molecule sweeteners (e.g.…”
Section: -2006mentioning
confidence: 99%
“…Sensitivity to brazzein requires the CRD of hT1R3 as well as the ATD of hT1R2 (15,16). The TMD of hT1R3 is required for sensitivity to cyclamate, neohesperidin dihydrochalcone, and the sweet inhibitor lactisole (17)(18)(19).…”
mentioning
confidence: 99%